Development, Neoliberalism, and Islamism in South Asia The Case of Bangladesh - Husain, Mustahid M. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"Very few studies have endeavoured to explore how neoliberal policies of the Bangladeshi state impacted institutions such as education and military, contributed to the othering in social milieu, and shaped the daily lives of the people. Mustahid untangles this relationship, analyzes them in-depth and challenges the conventional wisdom. Empirical data gathered from long field research has been weaved with the theoretical insights and offers a unique perspective." - Ali Riaz, Distinguished Professor of Political Science, Illinois State University, and President of the American Institute of Bangladesh Studies (AIBS) "Bangladesh has long been viewed as a donor darling in the international aid industry and a crucible for development programs, policies, and non-governmental organizations, yet poverty and inequality persists. Husain's book examines this puzzle and offers a theoretically rich and original interpretation of the history of development in Bangladesh and how the interplay of development, neoliberalism and Islamism have shaped the evolution of the Bangladeshi state, society, and economy in recent years." - Liam Swiss, President, Canadian Association for the Study of International Development (CASID) "A brilliant piece of scholarship! In juxtaposing the country at the crossroads of globalization with machinations by international and local interest groups, Mustahid has beautifully illustrated the complexity of the neoliberal problem." -Taj Hashmi, author of Fifty Years of Bangladesh, 1971-2021 This monograph explores dual hegemony and the politics of development in Bangladesh. The interdisciplinary research covers thematic areas of development, Islam-neoliberalism, and military's private sector engagements. This book is of interest to scholars of development studies, political Islam, and security studies, including terrorism and the politics of South Asia. Mustahid Husain is a scholar based at the University of British Columbia, Canada.
Chapter 1: Introduction -- Chapter 2: Development, Political Economy, and Neoliberalism -- Chapter 3: Neoliberalism, Class Structures and Politics of Development in Bangladesh -- Chapter 4: Neoliberalism, Infrastructure and Philosophical Poverty -- Chapter 5: Neoliberalism, Islam and Intolerance -- Chapter 06: Neoliberalism and the Political Economy of Bangladesh Military -- Chapter 7: Conclusion.
Keywords: Political science; Politics and International Studies